Biomass effects on oxygen transfer in membrane bioreactors - Germain, Eve; Nelles, F.; Drews, A.; Pearce, Peter; Kraume, M.; Reid, E.; Judd, Simon J.; Stephenson, Tom (Elsevier, 2007)
Ten biomass samples from both municipal and industrial pilot and full scale submerged membrane bioreactors (MBRs) with mixed liquor suspended solids concentrations (MLSS) ranging from 7.2 to 30.2 g L−1 were studied at six air-flow rates (0.7, 1.3, 2.3, 3, 4.4 and 6 m3 m−3 h−1). Statistical analyses were applied to identify the relative impacts of the various bulk biomass characteristics on oxygen transfer. Of the biomass characteristics studied, only solids concentration (correlated with viscosity), the carbohydrate fraction of the EPS (EPSc) and the chemical oxygen demand (COD) concentration of the SMP (SMPCOD) were found to affect the oxygen transfer parameters kLa20 (the oxygen transfer coefficient) and α-factor. The relative influence on kLa20 was MLSS>aeration>EPSc>SMPCOD and on α-factor was MLSS>SMPCOD>EPSc>aeration. Both kLa20 and α-factor increased with increasing aeration and EPSc and decreased with increasing MLSS and SMPCOD. MLSS was found to be the main parameter controlling the oxygen transfer.
Keywords: Oxygen transfer; MBR; Biomass; Aeration